Plug-in CSS [ 100 power solutions - Nixon, Robin , 1961- (McGraw-Hill, 2011)
"100 CSS and HTML power solutions in one handy guide Plug-in CSS is filled with with ready-to-use CSS and HTML solutions for creating dynamic websites. Save hundreds of hours of programming time! Make your website look great with custom fonts, animated menu systems, individually styled forms, and other effects. This practical guide shows you how to do all of these things and much more using simple style sheet plug-ins.This practical guide takes you through each example step by step so there?s no need to look up anything elsewhere. Every solution is complete and applicable immediately. The book can be dipped into as required with each chapter being self contained. Plus, you can download all the style sheets and HTML from the book?s companion website.Plug-in CSS Gives you 100 ready-to-use CSS and HTML solutions Solves a single problem or set of problems in each chapter with the entire solution available Features a companion website with all the book?s ready-to-run examples available for download Covers all the main dynamic features a webmaster needs to accomplish Practical, step-by-step coverage: CSS; Classes; Objects; Text and Typography; Menus and Navigation; Page Layout; Visual Effects; Dynamic Classes; Navigation; Incorporating JavaScript; Superclasses"--Provided by publisher